2007
DOI: 10.1002/col.20330
|View full text |Cite
|
Sign up to set email alerts
|

Global color impressions of multicolored textured patterns with equal unique hue elements

Abstract: A global color impression from a multicolored textured pattern can be identified. It is not clear, however, how such a single color impression can be determined from the elemental colors of the multicolored textured pattern. To investigate this question, two hypotheses were evaluated. The first hypothesis is that a single color impression is determined by the colorimetric average of the elemental colors in the textured pattern (colorimetric average hypothesis). The second hypothesis is that the impression is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…Kuriki [31] has shown that adjustments to mosaics with many tiny elements were not reflective of the colorimetric mean, being biased towards the most saturated element. However this was under continuous viewing conditions [see also 32], rather than the rapid-exposure of the ensemble perception paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Kuriki [31] has shown that adjustments to mosaics with many tiny elements were not reflective of the colorimetric mean, being biased towards the most saturated element. However this was under continuous viewing conditions [see also 32], rather than the rapid-exposure of the ensemble perception paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Although rigorous studies have been carried out in the fields of detection and discrimination of spatial periodic patterns [3]- [6], there have not been many studies of perceived color impression from mixed patterns in the mid-range spatial frequency in which the discrimination of patterns is rather obscure [7]- [9]. Kuriki reported that the mosaic element with the highest saturation strongly influences the perceived average color to represent a mosaic pattern [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also found that observers can approximate the colorimetric mean when adjusting a homogenous patch to represent a continuously presented multicolor mosaic but that these estimates are biased toward the salience or saturation of the mosaic elements (Kuriki, 2004) and the position of the unique hues (Sunaga & Yamashita, 2007)-i.e., the red, green, blue, or yellow that appears pure, unmixed with any other hue (see Kuehni, 2014). Such adjustments are also more variable when the perceptual distance between element colors is greater (Webster et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have probed directly for representations of the mean color (e.g., Kuriki, 2004;Sunaga & Yamashita, 2007;Webster et al, 2014) have allowed observers unlimited time to view the ensemble stimuli rather than using rapid presentation to encourage the deployment of distributed attention (e.g., Alvarez & Oliva, 2008;Baijal, Nakatani, van Leeuwen, & Srinivasan, 2013;Treisman, 2006). When rapid presentation has been used (e.g., de Gardelle & Summerfield, 2011;Maule et al, 2014;Michael et al, 2014), tasks have not probed directly for representations of the mean color.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation